Successfully Achieving Strategy Through Effective Portfolio Management - Parth, Frank R. (Issn Ser., 2021)
This book provides the approach that significantly increases an organization's ability to achieve its strategy. This is not a book about developing strategy. This is a book that will help you actually achieve the strategy the organization's leadership has developed. Strategy is necessary but it is a complete waste of time unless it is effectively turned into real results. If you want to see where an organization will be in 5 years, don't look at its strategic goals. Look at where management spends the money.